Quantitative assessment of volumetric muscle loss: Dual-energy X-ray absorptiometry and ultrasonography. (April 2021) - Minetto, Marco Alessandro; Busso, Chiara; Gamerro, Giulia; Lalli, Piera; Massazza, Giuseppe; Invernizzi, Marco
Abstract: The generalized skeletal muscle disorder that involves (in elderly subjects) the progressive loss of muscle mass and function has been defined sarcopenia, whereas the rapid-onset (traumatic or surgical) and focal (unilateral) loss of skeletal muscle with resultant functional impairment has been defined volumetric muscle loss. Different tools and approaches are commonly used in the clinical settings to quantify the loss of muscle or lean mass and to assess the consequent motor impairment. This review describes the technical principles and provides a summary of the main parameters that can be obtained to assess lean mass (and its distribution) or muscle size (and its structure) through the two imaging techniques most easily accessible and therefore frequently adopted in the clinical practice: dual-energy X-ray absorptiometry and muscle ultrasonography.